FOOD COURT UNM: PENGEMBANGAN APLIKASI PEMESANAN MAKANAN BERBASIS ANDROID DENGAN METODE AGILE : UNM FOOD COURT: DEVELOPMENT OF ANDROID-BASED FOOD ORDERING APPLICATION WITH AGILE METHOD - Muhammad Argya Yunansyah; Aqsa Mahmud; M. Aflah Ogi Daffa; Ilham Daffa Maulana; Andi Dio Nurul Awalia; Marwan Ramdhany Edy (CV. Sakura Digital Nusantara, 2025)
The food ordering system on campus is one example of how advances in information technology encourage the conversion of manual services into digital services. The traditional food ordering procedure at Makassar State University poses a number of problems, including long queues and slow service. The purpose of this project is to create UNM food court android application, an Android-based food ordering software, as a digital way to improve service effectiveness. The approach used is the Agile method which is an incremental and iterative approach, with many sprint cycles that allow for continuous assessment and improvement in response to customer requirements. Using black box and white box methodologies, the development process is run through planning, requirements analysis, interface design, implementation, and testing phases. The app can enable multi-role login functions, food ordering, order progress notifications, and real-time administration of stores and users, according to implementation results. Testing shows that each feature works as intended. This study concludes that the UNM food court app contributes significantly to the digitalisation of food ordering services on campus and the Agile method was successful in creating a mobile app based on real demand. Furthermore, this study contributes to the body of knowledge regarding the use of Agile approaches in software development for the field of education.